2004
DOI: 10.1677/joe.1.05599
|View full text |Cite
|
Sign up to set email alerts
|

Induction of glucose transporter 1 expression through hypoxia-inducible factor 1α under hypoxic conditions in trophoblast-derived cells

Abstract: Glucose transporter 1 (GLUT1) plays an important role in the transport of glucose in the placenta. During early pregnancy, placentation occurs in a relatively hypoxic environment that is essential for appropriate embryonic development, and GLUT1 expression is enhanced in response to oxygen deficiency in the placenta. Hypoxia-inducible factor-1 (HIF-1)alpha is involved in the induction of GLUT1 expression in other cells. The present study was designed to test whether HIF-1alpha is involved in hypoxia-induced ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
128
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(146 citation statements)
references
References 49 publications
14
128
2
2
Order By: Relevance
“…28 Previous studies have shown that CoCl 2 is just as efficient as low oxygen levels in inducing a hypoxic environment. In common with several previous studies, 29,30 which used both conditions in parallel, our data using either 1% oxygen or 150 mM CoCl 2 demonstrated similar results. This was the case with either HSVtk/GCV or NTR/CB1954 prodrug-activating system.…”
Section: Discussionsupporting
confidence: 91%
“…28 Previous studies have shown that CoCl 2 is just as efficient as low oxygen levels in inducing a hypoxic environment. In common with several previous studies, 29,30 which used both conditions in parallel, our data using either 1% oxygen or 150 mM CoCl 2 demonstrated similar results. This was the case with either HSVtk/GCV or NTR/CB1954 prodrug-activating system.…”
Section: Discussionsupporting
confidence: 91%
“…HRE-driven luciferase activity was enhanced by hypoxic conditions, and GLUT1 expression was stimulated by up-regulated HRE activity (Hayashi et al 2004). Farrell et al (2010) reported that TXNIP inhibited HRE-driven luciferase activity in a SV-40 transformed alveolar epithelial cell line (MLE-12) and the expression of the HIF target gene, VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…GLUT1 expression is regulated by a number of different mechanisms, for example, transcription factors such as Sp1, Sp3, and p53 (Behrooz and IsmailBeigi 1997;Schwartzenberg-Bar-Yoseph et al 2004;Hwang and Ismail-Beigi 2006). In addition, GLUT1 expression and glucose uptake are stimulated by hypoxia via induction of transcription factors, such as hypoxia induction factor 1-alpha (HIF-1-alpha), which increases GLUT1 promoter activity (Hayashi et al 2004). The binding site of HIF-1-alpha, namely the hypoxia response element (HRE), is present in the human and rat GLUT1 promoter regions (Behrooz and Ismail-Beigi 1997;Zelzer et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…3F), even at the highest concentration of 1 mM. To confirm the role of HIF-1α in the mechanism of action of indolepyruvate, we examined two HIF-1α target genes, glucose transporter 1 (GLUT1) and lactate dehydrogenase A (LDHA) (33,34). LPS induced the mRNA of both genes and this induction was inhibited in the presence of indolepyruvate (Fig.…”
Section: Indolepyruvate Alters the Glycolytic State Of The Cell Follomentioning
confidence: 98%